Postural reactions of girls and boys aged 12–15 years evaluated using the Romberg test - Wilczyński, Jacek; Ślężyński, Jan (Medical Studies/Studia Medyczne, 2016)
Introduction : The complex system controlling human posture includes a gaze stabilisation system, which comprises the control of direction and visual acuity during head and body movements, and a posture stabilisation system, keeping the body in balance at rest and in movement. Aim of the research: To analyse the postural reaction of SOX and SOY using the Romberg test with eyes open (EO) and closed (CE) in girls and boys aged 12–15 years. Material and methods : The study included 503 students of Primary School No. 13 and School No. 4 in Starachowice. Postural reactions were tested on a Cosmogamma platform by Emildue R50300. Postural reactions were analysed, and mean sway X (MSX) and mean sway Y (MSY) were calculated. Results: Analysis of variance showed significant differences of MSX only between girls and boys (p < 0.036). MSX was significantly lower in girls in both tests with EO and CE. Although there was no apparent significant difference of MSX between the Romberg test with EO and CE, a slight progression was observed in the test with CE. Analysis of variance of MSY with a single classification showed a significant effect of study options (p < 0.048), a significant interaction of gender and options of the study (p < 0.048), and a significant interaction of age and options of the study (p < 0.026). Analysis of variance of MSY showed a significant progression of MSY in the test with CE. Conclusions : Our research showed that balance with CE does not worsen, so it can be assumed that children have limited skills of using vision to maintain balance because there is a lack of appropriate coordination between vision and motor abilities, which in children are in development.